Karyological Studies of South American Rodents (Rodentia:Cricetidae) : I. Comparative Chromosomic Analysis in Scapteromys Taxa - Brum-Zorrilla, N. (1986)
South American rodents of the genus Scapteromys, are know to exist in a number of different chromosomal forms. S. tumidus has 2n = 24 from Uruguay while three different Brazilian taxa, all referred to as S. tumidus have respectively 2n = 36,34 and 24. S. aquaticus from Argentina has 2n–32. By G- band comparisons we find that the 2n = 24 S. tumidus from Uruguay and Brazil are chromosomically more closely related to S. aquaticus from Argentina than to alleged S. tumidus with 2n = 34–36 from Brazil. These results suggest that the latter may represent a new, still undescribed, species.